The effect of inhaled corticosteroid on salivary cytokine level in relation to Candida albicans among asthmatic children - Abdul Wadood, Meena O.; AL-Dahan, Zainab A.A. (AL-Kindy College Medical Journal, 2016)
Background: Asthma is a common chronic disease in children in which the body’s airways swell, preventing the lungs from filling with air, there are many different inflammatory cells involved in asthma which can synthesize and release cytokines which are recognized to be important in chronic inflammation and play a critical role in the inflammatory response. Objectives: to assess the local effect of ICS on oral tissue by measuring Interlukine-12 level and Candida albicans colony in saliva among12 year’s old asthmatic children who were collected from AL- Zahra Center Advisory for Allergy and Asthma, and compares them with non-asthmatic children of the same age and gender.Type of the study: Cross –sectional study.Methods: The total sample composed of 60 children 30 asthmatic children who received medium dose of ICS/day for two years and thirty non-asthmatic children. The unstimulated saliva was collected under standard condition and then analyzed for assessment of IL-12 level and Candida albicans colony. Results: Among asthmatic and non- asthmatic children; the mean rank of salivary IL-12 was found to be higher among C. albicans carrier group than without C.albicans with statistically highly significant difference (P< 0.01). Concerning each gender the same findings were recorded. Concerning IL-12 + and IL-12-, results reported that the mean rank differences were found statistically non-significant difference (P>0.05). Concerning each gender the same results were reported. Concerning gender differences, data analysis showed that there were no statistically significant differences. The results illustrated that the mean rank of salivary IL-12 was found to be higher among asthmatic than non- asthmatic children with statistically significant difference (P=0.016). Concerning each gender, similar results were recorded as the difference was not significant (P>0.05). For C.albicans carrier asthmatic and non- asthmatic children and total asthmatic and non- asthmatic children, the relation between the IL-12 concentration and C.albicans quantities were strong highly significant in positive directionConclusions: The findings of the present study showed that the asthmatic disease and oral candida colonization play an important role in elevation of the IL-12 level in saliva.